Echocardiographic predictors of worsening renal function in acute heart failure: observations from the RASHF registry - Soltani, Mohammad Hossein (ESC Heart Fail, 2018)
AIMS: Echocardiography is known as the most useful diagnostic test in the assessment of patients with heart failure (HF), and the prognostic significance of echocardiographic findings in HF is well known. In this report, we aim to present the prognostic significance of a limited set of echocardiographic parameters obtained within 24 h of admission of patients enrolled in the Rajaie Acute Systolic Heart Failure registry. METHODS AND RESULTS: A total of 230 patients with the diagnosis of acute systolic HF (left ventricular ejection fraction ≤ 35%) were enrolled into the study. Transthoracic echocardiography was performed for all study population within 24 h of admission. The primary endpoint of the study was the occurrence of worsening renal function (WRF) during the hospitalization course.Acquiring data of transthoracic echocardiography within 24 h of admission was feasible in all study participants. The median (inter‐quartile range) of left ventricular ejection fraction was 20% (15–23%). Severe right ventricular dysfunction was observed in 21.5% of patients. The grade of inferior vena cava collapse and right ventricular systolic dysfunction were associated with WRF. In multivariable analysis, right ventricular systolic dysfunction was among the independent predictors of WRF [β = 0.8, P = 0.01, odds ratio (OR) = 2.4 (1.2–4.9)] and in‐hospital mortality [β = 0.6, P = 0.04, OR = 1.5 (0.5–4.6)]. CONCLUSIONS: Echocardiographic parameters are useful for baseline assessment and provide additional information besides other clinical variables for prognostication. Right ventricular dysfunction is the most important risk factor in developing WRF and in‐hospital mortality in patients with acute HF.